Pengaruh Pemberian Jenis Pinang (Areca Catechu L.) yang Berbeda sebagai Feed Additive terhadap Produksi Karkas Ayam Broiler - Jaja, Katharina Dwi Apriyani; Suryatni, Ni Putu Febri; Theedens, Jonas F.; Armadianto, Heri (Animal Agricultura, 2024)
catechu L.) as a feed additive on broiler chicken production. This study use 96 broiler chickens CP 707. Analysis of variance used in this study was a completely randomized design (CRD), with 4 treatment and 6 replications. The treatments were T0: commercial feed without additives (control), T1: 1% betel nut powder, T2:1% areca nut irian and T3: 1% ornamential betel nut powder. The variables measured were the physical quality of the final body weight, carcass percentage, percentage of non carcass and abdominal fat percentage. The result of statistical analysis showed that the final weight had a significant effect (P<0,005) on broiler chicken and the percentage of carcass, non-carcass and abdominal fat had no significant effect (P>0,05). The conclusion was that of the three types of areca nut given, giving irian areca nut as a feed additive had a higher final body weight than giving other types of areca nut, but the three types of areca nut had the same effect on carcass percentage, non-carcass percentage and abdominal fat percentage.